2017
DOI: 10.18203/2320-1770.ijrcog20172944
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anaemia in adolescent girls

Abstract: Background: The world’s adolescent population is facing a series of serious nutritional challenges which are not only affecting their growth and development but also their livelihood as adults. Yet, adolescents remain a largely neglected, difficult to measure and hard to reach population, in which the needs of adolescent girls in particular, are often ignored. Anemia in adolescent girls contributes to maternal and foetal mortality and morbidity in future. The objective of the study was to estimate the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
(8 reference statements)
3
8
1
1
Order By: Relevance
“…e children of educated parents consume ironrich food, utilize adequate healthcare facilities, and manage hygienic household environment, which can be associated with reduction in anemia among adolescent girls. e findings are consistent with the studies [31,32], which reported that children of highly educated parents have lesser predisposition to develop anemia. Economic well-being of girls determined based on the father's, mother's, and family monthly revealed that all the independent variables are significantly associated with the prevalence of anemia among girls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…e children of educated parents consume ironrich food, utilize adequate healthcare facilities, and manage hygienic household environment, which can be associated with reduction in anemia among adolescent girls. e findings are consistent with the studies [31,32], which reported that children of highly educated parents have lesser predisposition to develop anemia. Economic well-being of girls determined based on the father's, mother's, and family monthly revealed that all the independent variables are significantly associated with the prevalence of anemia among girls.…”
Section: Discussionsupporting
confidence: 92%
“…Parental, household, and community factors are associated with anemia [25,[31][32][33][34][35][36][37][38][39][40][41]. e findings of our study elucidated that prevalence of anemia was smaller among girls whose parents had attained more than 12 years of education.…”
Section: Discussionmentioning
confidence: 89%
“…Also mean BMI was low in severely anemic subjects as compared to mild-moderate anemic group. This finding is in agreement with Upadhyay et al, Talpan et al & Hanan et al [9,13,14]. Low BMI in severe anemia suggests that anemia affects the overall growth of adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…According to NFHS 3 more than 39% adolescent girls are mildly anemic while 15 % and 2% have moderate and severe anemia respectively [3]. Similarly 2% to 4% prevalence of severe anemia was noted by other authors too [8][9][10]. Ours was a hospital based study which can be the reason of high prevalence of severe anemia.…”
Section: Discussionmentioning
confidence: 67%
“…Majority of girls 266 (34.55%) in present study were mildly anaemic and this is consistent with findings of Siva PM et al in Kerala, Singla N et al in Ludhiana, Upadhye JV et al in Nagpur and other studies in different parts of India where mild anaemia is found to be most prevalent. [9][10][11] Using HCS, Verma R et al found similar magnitude of problem of anaemia among adolescents including boys in Rohtak. 12 However, in a study by Deshpande NS et al in Pune, majority had moderate anaemia.…”
Section: Discussionmentioning
confidence: 99%